2002
DOI: 10.1063/1.1471577
|View full text |Cite
|
Sign up to set email alerts
|

Structure-sensitive oxidation of the indium phosphide (001) surface

Abstract: The oxidation of anion-and cation-rich indium phosphide ͑001͒ has been investigated by exposure to unexcited molecular oxygen. Indium phosphide oxidation is an activated process and strongly structure sensitive. The In-rich ␦(2ϫ4) surface reacts with oxygen at 300 K and above. Core levelx-ray photoemission spectra have revealed that the O 2 dissociatively chemisorbs onto the ␦(2ϫ4), inserting into the In-In dimer and In-P back bonds. By contrast, the P-rich (2ϫ1) reconstruction does not absorb oxygen up to 5ϫ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 43 publications
12
56
2
2
Order By: Relevance
“…On other surfaces where M -M dimers are not present, M -O-P bonds should dominate. These conclusions are consistent with suggestions from several experiments on InP and GaP oxidation 23,24,26,[66][67][68][69] . However, we should note that for the (100) surface, M -O-M is an exclusively surface-adsorbed topology, whereas M -O-P features oxygen incorporated in the subsurface.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…On other surfaces where M -M dimers are not present, M -O-P bonds should dominate. These conclusions are consistent with suggestions from several experiments on InP and GaP oxidation 23,24,26,[66][67][68][69] . However, we should note that for the (100) surface, M -O-M is an exclusively surface-adsorbed topology, whereas M -O-P features oxygen incorporated in the subsurface.…”
Section: Discussionsupporting
confidence: 82%
“…Of the possible oxygen local bond configurations, two should dominate oxygen chemisorption and subsequent native oxide nucleation based on their relative stability: M -O-P and M -O-M . Notably, these same two topologies have been suggested based on x-ray photoemission spectra of InP(001) 23 , as well as calculations on InP nanowires 65 . Both topologies can also branch to form an additional M -O bond with some cost in energy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dangling bonds of surface In atoms react with water, introducing O atoms into the In-P bonds to form In-O-P bonds. 29 This process is energetically more favorable than the formation of In-O-In or P-O-P bonds. 30 It was reported that the anodization of InP leads to the formation of compositionally inhomogeneous oxides.…”
Section: Structural Chemical and Electronic Properties-mentioning
confidence: 99%